Evaluasi Kinerja Keuangan pada Pengembangan Jaringan 4G PT. Telekomunikasi Indonesia di Singaraja - Ni Wayan Novi Budiasni; Ni Made Sri Ayuni; Ni Kadek Ayu Trisnadewi (Jurnal Akuntansi Profesi, 2020)
This study aims to examine the significance of differences in financial ratios before and after the 4G network on the CV. Akar Daya Mandiri in the City of Singaraja, which is a product distribution from PT. Telekomunikasi Indonesia in Singaraja. Different test results using the Paired Samples Test found that the current ratio, debt to assets ratio, inventory turnover, and net profit margin have significant differences before and after the 4G network on the company's financial performance. While the debt to equity ratio, total assets turn over, return on assets, and return on equity have insignificant differences before and after the 4G network on the company's financial performance. Based on the value of the ratio owned by the company after being compared with industry standards, it is known that it still needs to be evaluated on the company's financial performance, before and after the 4G network. Because the ratio is still below the industry average standard. This condition indicates the need for increased management efficiency in the composition of debt, assets and company capital